Perancangan Ulang Gudang Waste untuk Mengurangi Risiko Kecelakaan Kerja Mengunakan Metode Class Based Storage dan 6S (Studi Kasus PT. RPG) - Muhammad Tarigan, Febbry; Nur, Muhammad; Surraya Lubis, Fitriani; Yola, Melfa; Harpito, Harpito (Fakultas Teknik Universitas Tulang Bawang, 2026)
High and continuous production processes inevitably generate large amounts of production waste. PT RPG is facing problems, especially with the warehouse used to store production waste which holds 17 types of waste. The warehouse is very small, with an area of only 16 m², so it cannot accommodate all 17 types of waste. This causes difficulties in waste placement activities, creates an irregular layout, and increases the risk of work accidents. The purpose of this study is to redesign the waste warehouse in order to reduce the risk of work accidents using the Class-Based Storage method and the 6S approach. This research is quantitative and involves steps such as frequency calculation, cumulative frequency, ABC classification, proposed 6S design, and proposed 3D layout model. The results showed that the warehouse area was expanded from 16 m² to 40 m², which improved the layout for material movement based on the Pareto 80/20 principle used in the ABC classification. In addition, there was a 46% increase in the efficiency of waste placement time, which supported more effective waste handling and retrieval, ultimately reducing the risk of workplace accidents. Thus, the Class-Based Storage and 6S methods proved effective in addressing the layout and safety issues at PT RPG's warehouse. Keywords: CBS, Layout, Warehouse, 6S